2015
DOI: 10.1200/jco.2014.57.4970
|View full text |Cite
|
Sign up to set email alerts
|

KIT and PDGFRA Mutations and the Risk of GI Stromal Tumor Recurrence

Abstract: GISTs with an identical KIT or PDGFRA mutation may have widely varying risks for recurrence. Most of the patients with PDGFRA mutations and those with KIT exon 11 duplication mutation or deletion of one codon have favorable RFS with surgery alone and are usually not candidates for adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
151
2
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 35 publications
8
151
2
16
Order By: Relevance
“…7,15,18,21,31 The higher PDGFRA mutation frequency observed in gastric GISTs is in accordance with the better prognosis observed for this type of tumor. 12,30,32 Our study revealed the potential prognostic relevance of the type and position of KIT mutations in untreated resected gastric GISTs, in addition to classic pathological criteria such as dimension, mitosis, Miettinen risk stratification, ulceration and necrosis.…”
Section: Discussionsupporting
confidence: 67%
“…7,15,18,21,31 The higher PDGFRA mutation frequency observed in gastric GISTs is in accordance with the better prognosis observed for this type of tumor. 12,30,32 Our study revealed the potential prognostic relevance of the type and position of KIT mutations in untreated resected gastric GISTs, in addition to classic pathological criteria such as dimension, mitosis, Miettinen risk stratification, ulceration and necrosis.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have demonstrated that activating mutations in the receptor tyrosine kinases KIT and PDGFRA are critical for the pathogenesis of GISTs (23)(24)(25). Recent studies have shown the important function of ETS variant 1 (ETV1), an ETS family transcriptional factor, in the progression of GISTs, and suggested that targeting both KIT and ETV1 may be effective for the treatment of this type of tumor (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The Contica GIST study (15), clearly showed that gastric GIST with a KIT del 557-558 had an inferior disease free survival compared to other mutants. A larger study, comprising 11 population based series (n=3,067; mutation analysis-1505), but untreated with IM, concluded that patients with PDGFRA mutations and those with KIT exon 11 duplication/single codon deletion mutations have a favorable recurrence free survival (RFS) with surgery alone (20). Conversely, in the adjuvant setting in operated tumors, mutation status has not replaced standard criteria with regard to the need for adjuvant IM, although data from long term follow up of the ACOSOG Z9001 Trial has suggested that KIT exon 11 deletions had maximal benefit from 1 year of adjuvant IM compared to other molecular subsets (21).…”
Section: Discussionmentioning
confidence: 99%